Cross-border acquisitions and profitability of acquired companies in Serbian cement industry - Marković , Dušan; Savović, Slađana (Anali Ekonomskog fakulteta u Subotici, 2022)
Transition to market economy in the Republic of Serbia started with one decade of delay compared to most former socialist countries. The transition has implied liberalization of economic policies in the area of foreign direct investments, even in some industries that have been previously considered strategic. Multinational companies have used new business opportunities and acquired some of the most important and largest domestic companies. This paper analyzes the impact of cross-border acquisitions on the profitability of targets in Serbian cement industry during the period 2000-2020. Serbian cement industry includes three cement companies, all of which were acquired in the process of privatization during 2002. The study analyzes changes of ROA (return on assets), ROE (return on equity) and ROS (return on sale) of targets in the short term and in the long term after the acquisitions. The research results show that profitability of all companies improved both in the short term and in the long term after acquisitions. These improvements were achieved through higher cost efficiency and more efficient business asset management.